Arthropod Pest Management in Organic Vegetable Greenhouses - Weintraub, Phyllis G.; Recht, Eitan; Mondaca, Lilach Lily; Harari, Ally R.; Diaz, Beatriz Maria; Bennison, Jude (2018)
We present a comprehensive discussion of pest management in organic greenhouse vegetable production. Greenhouse structures and production practices vary greatly in different regions of the world. In northern Europe and North America, they are closed heated structures because of the long periods of cold weather and biological control is highly developed. In Israel, commercial greenhouses are made of netting or plastic, are not heated because the winters are generally mild in comparison with northern climes and hot in the summers, and biological control is used almost exclusively on some crops. In South America, greenhouses are simple structures covered with plastic material without nets or heating/cooling systems. We limit our discussion to properly closed and ventilated greenhouses, exclusive of structures that are opened for any period during the day or season. Our discussion covers greenhouse structure; the first line of defense, regulatory, and phytosanitary measures; various management methods; and finally specific management of primary pest groups, mites, thrips, hemipterans (aphids, mealybugs, and whiteflies), and small Lepidoptera.